2002
DOI: 10.1007/s00132-001-0289-2
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss von Design und Implantationstechnik auf das Risiko der progredienten Sinterung verschiedener HWS-Cages

Abstract: The aim of this study was to compare the subsidence of differently designed cervical interbody fusion devices under defined conditions. Forty-five bovine vertebral bodies were dissected from soft tissue and cartilage. The bony end plate was then taken off by 0, 1, and 2 mm. Five vertebral bodies of each abrasion depth were prepared for the uptake of a fusion device. Thus, three different fusion devices of comparable size underwent biomechanic testing in a Zwick testing machine with 4000 cycles of axial compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
1
11
0
3
Order By: Relevance
“…Several studies have asserted that the preparation of the endplates has an influence on subsidence [7, 11-13]. And at least one study has stated that excessive distraction of the intervertebral space has an influence on the probability of subsidence [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have asserted that the preparation of the endplates has an influence on subsidence [7, 11-13]. And at least one study has stated that excessive distraction of the intervertebral space has an influence on the probability of subsidence [14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…However, not mentioned at all in the literature are comparable biomechanical investigations between ALIF with and without endplates using parameters (ROM, NZ, stiffness), which characterize the stability of the motion segment. A number of studies have made comparisons between the different cages in conjunction with ALIF and with the physiologic specimens [15,25,26,37]. In 2000, Kanayama et al undertook biomechanical investigations on calves using six different cages, one of which was the Harms cage, and observed no statistically significant differences [25].…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic study by Ba¨erlocher et al 6 a significant lower subsidence rate has been noticed in patients undergoing anterior arthrodesis using titanium or Polymethyl-methacrylate (PMMA)-cages in comparison without implant or with autogenous bone graft. Another study carried out by our group 37 showed a correlation between the spacer material and the subsidence rate. Spacer configuration with enhanced surface structuring or small surface area showed a higher subsidence rate.…”
Section: Outcome Versus Subsidence Of the Intervertebral Spacer In Thmentioning
confidence: 94%
“…Spacer configuration with enhanced surface structuring or small surface area showed a higher subsidence rate. 37 regards an over distraction a potential hazard for subsidence. Brower and colleagues 42 identified that a distraction of more than 4 mm of the original height could set a trend of nonfusion.…”
Section: Outcome Versus Subsidence Of the Intervertebral Spacer In Thmentioning
confidence: 98%